Prospective regional landscape parks – reserves for optimization of the reserve and ecological network of Ternopil region - Tsaryk, L. P.; Kuzyshyn, A. V.; Tsaryk, P. L. (Man and Environment. Issues of Neoecology, 2025)
Purpose. Development of ways of functional-spatial improvement of reserve and ecological networks by involving promising regional landscape parks of Ternopil region for preservation. Methods. The methodological basis of the study is the conceptual provisions of the functional-spatial features of the functioning of regional reserve and ecological networks, with the definition of the reserve and recreational potential of natural complexes and human potential of urban settlements, taking into account the peculiarities of their relationship with urban settlements, transport network, recreational infrastructure, functional fullness, completeness, degree of connectivity using the graph method. Results. The creation of the proposed network of regional landscape parks will significantly improve the preservation of 21 territorial communities, which is 38% of the territorial communities of the region. Of the 21 territorial communities, 16 have a low preservation index. After taking into account the potential reserve, this indicator increases by nine, and in some places by ten or more times (Vyshnivetska, Skala-Podilska, Bilobozhnytska, Mykulynetska, Narayivska, Zborivska territorial communities). Three territorial communities will have a reserve indicator of the European level (Zalozetska, Berezhanska, Chortkivska). Given the presence of significant natural and historical and cultural recreational resources in them, there are all prerequisites for developing various types of recreation and tourism. The presented maps of the reserve of territorial communities demonstrate that the creation of promising 20 regional landscape parks significantly differentiates them in terms of reserve indicator. At the same time, the reserve area in the region will increase, the reserve of the region will increase from 8.95% to 14.21%. Conclusions. The proposed course of events contributes to the improvement of the territorial organization of the reserve and ecological networks from the local to the regional levels, the activation of the tourist and recreational activities of the economic sector, involving the potential of territorial communities in this sphere.